Strategic human resource development – a manoeuvre for future competencies - Parameswaran, Hima (Serbian Journal of Management, 2020)
The changing role and function of Human Resource Development professionals due to social, economic, political and technological alterations lead the way for strategic HRD practices in organizations. In this current world of industrialization, this term relates to the achievement of competitive benefits by aligning organizational goals and priorities with structured and future-oriented activities. A study on strategic HRD lends a hand to eliminate the hitches of an organization by rational planning and people development with a focus on predictability and consistency. This research not only enlightens the implication of strategic activities but also it strengthens individual creativity, knowledge management, career planning, and individual competencies amongst employees in industrial sectors. It highlights on the employee perception about these SHRD practices of companies, which is a fundamental factor for the employee contentment, performance, and for the necessity of socio-technical systems. Accordingly, the study is focused at Dubai, U.A.E., in the shape of “Strategic Human Resource Development – A manoeuvre for future competencies” with a sample size of 300 from various companies by quantitative and qualitative analysis. Accordingly, it has been statistically confirmed that four independent variables show a positive relationship with strategic HRD activities. Along with this, it identifies the extent to which the HRD and its related work-life factors are provided by the selected companies. The result of the survey generated a key model and a framework for SHRD by creating a valuable contribution to the organization in facing the future challenges.